Research output of librarians in agricultural research institutes in Nigeria, 2003-2008 (2012)
This study investigated the research output of librarians in Agricultural Research Institutes (ARI) in Nigeria between 2003-2008 with special reference to Oyo and Edo States. A survey research design was employed and the instruments used for data collection were questionnaire and interviews. 20 out of the 22 librarians in the selected Agricultural Research Institutes completed the questionnaire, thus giving a response rate of 90.91%. Simple percentages, pie chart as well as bar charts were used for the presentation of the data collected. Some of the major findings of the study include the following: the more experienced librarians published more than their other less experienced colleagues, publication output was the least used criterion for the promotion of librarians in the Agricultural Research Institutes, and the major challenge to librarians was lack of funds to support research activities. In the light of these findings, some recommendations were proffered to enhance the research output of the librarians. Among these include: that publication should be regarded as a vital criterion for promotion of librarians; librarians should be encouraged to conduct research and publish their findings since research is the focus of their institutes; and librarians should be assisted to attract grant for their research activities